Hubungan Tingkat Pengetahuan Ibu Tentang Makanan Pendamping ASI Dengan Pemberian Makanan Pendamping ASI Pada Bayi 6-12 Bulan Di Klinik BPS Sulastri Kecamatan Marelan Kota Medan Tahun 2023 - Elsa Nianda Hasibuan; Asnita Sinaga; Rumondang Sitorus; Kamelia Sinaga (NAJ Nursing Applied Journal, 2024)
MP Giving breast milk too early at less than 6 months of age is an indicator that the mother has failed to breastfeed exclusively, which also has an impact on the rate of exclusive breastfeeding which is still low. Providing early MP-ASI is closely related to the decisions made by the mother. Giving MP-ASI too early can have an impact on the baby's health, including other diarrheal diseases. This is because the baby's digestive system is not ready to accept food other than breast milk, causing a reaction in the digestive system (Utami, 2019). Giving people MP-ASI too early is a difficult problem. Even though breast milk is known to have many advantages in terms of nutrition, immunity, economics, practicality and psychology, mothers' awareness of giving breast milk is still very low. The practice of giving MP-ASI too early, namely to babies less than 6 months old, is a serious concern because the digestive organs in the baby's body have not yet fully developed. This is caused by several reasons, including because mothers' knowledge about the importance of breastfeeding is still low, lack of family support for exclusive breastfeeding, and many mothers work outside the home (Yuliarti, 2019). An initial survey was conducted at the BPS Sulastri Clinic, Medan Marelan District, Medan City on mothers who had babies aged 6-12 months. Of the 12 mothers who conducted interviews, there were 7 mothers who gave MP-ASI to babies before the age of 6 months, and 5 mothers said that the baby has been given formula milk since birth because only a little breast milk comes out. From the results of this background, the author is interested in researching "The relationship between the level of maternal knowledge about complementary foods for breast milk and the provision of complementary foods for babies aged 6-12 months at the BPS Sulastri Clinic, Medan Marelan District, Medan City in 2023."